Pengaruh Strategi Promosi, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Kasus Pada Pelanggan Restotan Cepat Saji Mcdonald’s Di Jababeka Cikarang) - Hafiz Dwi Septadianto; Pupung Purnamasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the influence of promotional strategies, price, and service quality on customer satisfaction at the McDonald's fastfood restaurant in Jababeka Cikarang. The research method used is quantitative, with data collection techniques through questionnaires distributed to 100 McDonald's customers in the area. Data analysis was conducted using SmartPLS 3 software to test the relationship model between variables. The results of the 1) study indicate that promotional strategies have a positive and significant effect on customer satisfaction. 2) Price was also found to have a positive and significant effect on customer satisfaction. Additionally, 3) service quality has a positive and significant effect on customer satisfaction. 4) Overall, these three variables promotional strategies, price, and service quality simultaneously influence customer satisfaction at McDonald's in Jababeka Cikarang. These findings suggest that to enhance customer satisfaction, McDonald's management needs to continually optimize promotional strategies, set competitive prices, and maintain as well as improve the quality of service provided. This study provides practical contributions to the management of fastfood restaurants in terms of improving customer satisfaction through effective marketing strategies, appropriate pricing, and high-quality service.